2015
DOI: 10.1371/journal.pntd.0003588
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ergosterol Biosynthesis in Leishmania donovani: Essentiality of Sterol 14alpha-demethylase

Abstract: Leishmania protozoan parasites (Trypanosomatidae family) are the causative agents of cutaneous, mucocutaneous and visceral leishmaniasis worldwide. While these diseases are associated with significant morbidity and mortality, there are few adequate treatments available. Sterol 14alpha-demethylase (CYP51) in the parasite sterol biosynthesis pathway has been the focus of considerable interest as a novel drug target in Leishmania. However, its essentiality in Leishmania donovani has yet to be determined. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 59 publications
2
76
0
1
Order By: Relevance
“…in 2015 who found that L . donovani parasites were able to tolerate > 50% reduction in CYP51 protein levels with no apparent effects on parasite phenotype [11]. These authors finally confirmed essentiality of CYP51 in Leishmania by obtaining complete loss of chromosomal CYP51 genes only in the presence of an episomal source of CYP51.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…in 2015 who found that L . donovani parasites were able to tolerate > 50% reduction in CYP51 protein levels with no apparent effects on parasite phenotype [11]. These authors finally confirmed essentiality of CYP51 in Leishmania by obtaining complete loss of chromosomal CYP51 genes only in the presence of an episomal source of CYP51.…”
Section: Discussionmentioning
confidence: 87%
“…brucei BSF. As Tb CYP51 and Ld CYP51 proteins share 84% of identity, we used the anti- Ld CYP51 antibody described by McCall and colleagues [11] to probe the kinetoplastids used in this study by western-blot. A band at the expected size was observed demonstrating that Tb CYP51 is expressed in T .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations